PROGRAM STUDI INTENSIF GURU DALAM MENINGKATKAN KINERJA MUROBBI DAN MUROBBIYAH DI SEKOLAH MENENGAH ATAS ISLAM TERPADU DINIYYAH AL-AZHAR JAMBI - Susanti, Ekalia; Arifullah, Mohd.; MY, Mahmud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the Intensive Teacher Study Program (Program Studi Intensif Guru/SIG) in improving the performance of male and female religious educators (murobbi and murobiyah) at SMA IT Diniyyah Al-Azhar Jambi. The objectives of this research are to describe the implementation of the SIG program, analyze its effectiveness in enhancing educators’ performance, and identify the supporting and inhibiting factors affecting its implementation. This study employed a qualitative approach with a descriptive research design. The research subjects included the principal, the SIG program coordinator, and murobbi and murobiyah. Data were collected through observation, in-depth interviews, and documentation, while data analysis was conducted using the Miles and Huberman qualitative analysis model. The findings reveal that the implementation of the SIG program has been carried out systematically through structured planning, implementation, and evaluation stages. The program has proven effective in improving the performance of murobbi and murobiyah, particularly in strengthening competencies in Qur’anic memorization (tahfidz), Arabic, and English, as well as enhancing their ability to integrate Islamic values into the teaching and learning process. Supporting factors include strong leadership support, a conducive school environment, and adequate facilities and infrastructure. Meanwhile, inhibiting factors consist of varying levels of teacher motivation, differences in participants’ initial competencies, and limitations in time allocation and instructional methods. The study concludes that the SIG program contributes significantly to improving educator performance, although further optimization is needed in technical implementation and participant motivation to maximize program outcomes.